Kilconnell Franciscan Friary, north nave wall, tomb niche, jamb and arch - O'Donovan, Danielle (My University, 2009)
Jamb, arch and hood moulding of flamboyant tomb niche. Moulding of jamb and arch from intrados comprises: ogee, quadrant, hollow chamfer, ogee. The hood, from extrados, comprises: quadrant, hollow chamfer, right-angled rebate, ogee. Ogees often occur in conjunction with this kind of elaborate flame like tracery, as at St. Nicholas, Galway.
Tomb niche
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Funerary monuments; Late Medieval; moldings, ogee; moldings, hollow; fillets (moldings); hood moldings